2020
DOI: 10.1101/2020.01.29.923714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fragmentation of extracellular ribosomes and tRNAs shapes the extracellular RNAome

Abstract: A major proportion of extracellular RNAs (exRNAs) do not co-isolate with extracellular vesicles (EVs) and remain in ultracentrifugation supernatants of cell-conditioned medium or mammalian blood serum. However, little is known about exRNAs beyond EVs. We have previously shown that the composition of the nonvesicular exRNA fraction is highly biased toward specific tRNA-derived fragments capable of forming RNase-protecting dimers. To solve the problem of stability in exRNA analysis, we developed RI-SEC-seq: a me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(42 citation statements)
references
References 92 publications
8
34
0
Order By: Relevance
“…To test this hypothesis, we added recombinant ribonuclease inhibitor (RI) directly to the cell-conditioned medium of different mammalian cell lines. To our surprise, addition of RI dramatically changed extracellular RNA profiles [119]. Without RI, most exRNAs outside EVs were 30-31 nt 5ʹ tRNA halves derived from acceptors of glycine and glutamic acid, as has been described in previous sections of this review.…”
Section: Biogenesis Of 5ʹ Trna Halves In the Extracellular Spacesupporting
confidence: 52%
See 3 more Smart Citations
“…To test this hypothesis, we added recombinant ribonuclease inhibitor (RI) directly to the cell-conditioned medium of different mammalian cell lines. To our surprise, addition of RI dramatically changed extracellular RNA profiles [119]. Without RI, most exRNAs outside EVs were 30-31 nt 5ʹ tRNA halves derived from acceptors of glycine and glutamic acid, as has been described in previous sections of this review.…”
Section: Biogenesis Of 5ʹ Trna Halves In the Extracellular Spacesupporting
confidence: 52%
“…However, the authors of this study purified EVs by ultracentrifugation, which results in less pure preparations compared to the density gradient method used in [72]. We have combined density gradient separation with non-radioactive digoxigenin-based Northern blot, and found that, indeed, EVs from nonstressed cells contain mostly full-length tRNAs instead of tRNA-derived fragments [119]. We will resume this discussion in chapter six.…”
Section: Evs Contain More Full-length Trnas Than Trna-derived Fragmentsmentioning
confidence: 98%
See 2 more Smart Citations
“…To be sure, EV association may not be needed to trigger responses. In addition to being loaded into EVs [17], noncoding RNA species from MCF-7 cells, mainly dimers of tRNA-Gly-GCC halves and ribosomal RNA, are also released in non-EV fractions [18]. In this form, they can activate primary bone-marrow-derived dendritic cells and induce the release of IL-1β.…”
Section: Shielding and Chemical Modification Of Rna: Molecular Contexmentioning
confidence: 99%